Preparation Calcium Oxide From Chicken Eggshells - Risfidian Mohadi; Kiki Anggraini; Fahma Riyanti; Aldes Lesbani (Sriwijaya Journal of Environment, 2016)
Abstract: The preparation of metal oxide CaO from chicken eggshell has been carried out by decomposition at various temperatures 600, 700, 800, 900, and 1000oC. The metal oxide CaO was characterized using XRD. Furthermore, The optimum temperature for preparation of CaO was determined based on the XRD pattern, then the characterization of CaO was extended using FT-IR spectrophotometer and BET analysis. The results show that the optimum temperature for preparation of CaO from chicken eggshell is 900oC with peak of 2Ө at 32.3o, 37.4o, 53.9o, 64.2o and 67.5o, respectively. The FT-IR spectrums show the unique vibration for Ca-O at 393 cm-1. The BET analysis show that CaO has surface area 68 m2/g with pore volume 1.65 cm3/g and pore size 6.6 nm which can be classified as mesoporous.Keywords: eggshell, base catalyst, CaO, BET, mesoporous Abstrak (Indonesian): Pembuatan oksida logam CaO dari cangkang telur ayam telah dilakukan melalui dekomposisi pada berbagai suhu 600, 700, 800, 900, dan 1000°C. Oksida logam CaO dikarakterisasi dengan XRD. Selanjutnya, Suhu optimum untuk persiapan CaO ditentukan berdasarkan pola XRD, setelah itu karakterisasi CaO dilanjutkan menggunakan FT-IR spektrofotometer dan analisis BET. Hasil penelitian menunjukkan bahwa suhu optimum untuk pembentukan CaO dari cangkang telur ayam adalah 900°C dengan puncak 2Ө muncul di 32.3°, 37.4°, 53.9°, 64.2° dan 67.5°. Spektrum FT-IR menunjukkan vibrasi unik untuk Ca-O di 393 cm-1. Analisis dengan BET menunjukkan bahwa CaO memiliki luas permukaan 68 m2/g dengan volume pori 1,65 cm3/g dan ukuran pori 6,6 nm yang dapat diklasifikasikan sebagai mesopori.Kata kunci: kulit telur, katalis basa, CaO, BET, mesopori